2022
DOI: 10.3390/ijerph19148707
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rice Yields and Critical N Losses from Paddy Soil under Different N Fertilization Rates with Iron Application

Abstract: The application of iron powder stimulated the growth of iron-reducing bacteria as a respiratory substrate and enhanced their nitrogen (N)-fixing activity in flooded paddy soils. High N fertilization (urea) in the flooded paddy soils has caused adverse environmental impacts such as ammonia (NH3) volatilization, nitrous oxide (N2O) emissions, and nitrate (NO3−) leaching. This study aims to investigate the effects of N fertilization rates in combination with an iron amendment on rice yields and N losses from floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In our field experiment, a significant increase in soil nitrogen-fixing activity was also observed after the application of iron powder to straw-returned paddy field soil [25]. Another field experiment in China demonstrated that a combination of iron application with 60-80% of the conventional nitrogen fertilization rate could maintain rice yields similar to those of the conventional nitrogen fertilization rate while reducing critical nitrogen losses in flooded paddy fields [26]. These studies strongly suggested that iron application to paddy soil increased the amount of nitrogen fixed in the soil by enhancing nitrogen fixation by iron-reducing bacteria.…”
Section: Introductionsupporting
confidence: 65%
“…In our field experiment, a significant increase in soil nitrogen-fixing activity was also observed after the application of iron powder to straw-returned paddy field soil [25]. Another field experiment in China demonstrated that a combination of iron application with 60-80% of the conventional nitrogen fertilization rate could maintain rice yields similar to those of the conventional nitrogen fertilization rate while reducing critical nitrogen losses in flooded paddy fields [26]. These studies strongly suggested that iron application to paddy soil increased the amount of nitrogen fixed in the soil by enhancing nitrogen fixation by iron-reducing bacteria.…”
Section: Introductionsupporting
confidence: 65%
“…Moreover, nitrogen-fixing bacteria have long been considered useful microorganisms for improving soil nitrogen fertility, and methods to promote their activity have been developed for sustainable agriculture [64]. For example, in paddy soils, recent studies showed that application of iron-bearing materials could enhance the nitrogen-fixing activities of indigenous iron-reducing bacteria within the families Anaeromyxobacteraceae and Geobacteraceae and maintain rice yields under reduced nitrogen-fertilizer application [65,66]. Given the ubiquity of iron-reducing diazotrophs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This damages the rice plant throughout their growth cycle. Flooding constrains the nutrient availability and limits the effective use of organic and chemical fertilizers resulting in decreased N use efficiency and N losses through NH3 volatilization, N2O emissions, and NO3 leaching causing environmental pollution [5,6]. Salinity increases transpiration demands through higher concentration of Na + and Clions and disturbs the…”
mentioning
confidence: 99%